Antibiotic Sensitivity and Antilysozyme Activity of Staphylococcus aureus Strains Isolated from the Blood of Patients with Sepsis - Z. F. Kharaeva; D. A. Elgarova; N. O. Kablakhova; L. Z. Blieva; E. B. Barokova; Z. A. Kambachokova; D. A. Elmurzaeva (Антибиотики и Химиотерапия)
Effective antibiotic therapy requires reliable data on the dynamics of sensitivity changes in each region. The aim of the study was to determine the sensitivity to antibiotics and antilysozyme activity of Staphylococcus aureus strains isolated from the blood of patients with sepsis over the period from 2017 to 2019. An increase in the resistance of Staphylococcus aureus to ceftriaxone, cefixime vancomycin, azithromycin, and levofloxacin was noted. Given the high incidence of resistance, the use of these drugs should be limited. Ceftazidime, tigecycline, daptomycin, and linezolid can be considered drugs of choice in empiric therapy of septic diseases of staphylococcal etiology. Most of the isolated strains exhibited antilysozyme activity (ALA). Most commonly the cultures had medium to high ALA scores.